Universidad y televisión: retos de la difusión científica en Aragón. - Ibarra-Arias, Rocío; Marta-Lazo, Carmen (Revista Latina de Comunicación Social, 2026)
Introduction: This study is part of a doctoral research project on the social transfer of scientific information in Aragon. It analyzes the journey of science generated at the University of Zaragoza until its appearance on regional television, highlighting the importance of strengthening the link between the research community and the media to foster a more informed citizenry. Methodology: A qualitative exploratory-descriptive design was applied, involving in-depth interviews with journalists, institutional stakeholders, and science communication personnel, as well as a focus group with university researchers. Thematic coding and data triangulation were used to identify barriers and proposals for improving science dissemination. Results: Key obstacles identified include the lack of specialization and resources in newsrooms, weak connections between scientists and journalists, the perceived low public interest in scientific topics, and the need for communication training among both journalists and researchers. Suggested improvements include more accessible press releases, the creation of stable media spaces dedicated to science, and joint training programs. Discussion: The findings align with previous studies that show the marginalization of science on television and emphasize the need for scientific media literacy. Institutional collaboration and training in science communication are highlighted as essential strategies to reverse this trend and strengthen scientific culture. Conclusions: This research provides a solid foundation for implementing strategies to enhance the visibility of science in Aragon, promoting cooperation between universities and media outlets, the development of content tailored to television formats, training in science communication, and the establishment of dedicated spaces that support a critical, informed, and engaged society.